Easy estate advertising services : www.sweethomes2u.com - Mansor, Siti Aishah (2007)
The Commercializing Estate Service Online: www.sweethomes2u.com is one of the alternatives for web based users. The main reason of developing the system is to provide a platform for commercializing real estates properties by real estate companies, estate agents and individuals who are interested. Nowadays, a lot of commercializing estate activities are very limited to traditional ways of commercializing. With the system, commercializing estate companies can promote their estate online with low cost. Furthermore, the system also integrates the Multimedia Message Service technology. The system is being developed by using the Unified Modelling Language together with Pretext Hyper Processor and MySQL Database. Other softwares that being used are Windows XP, Macromedia Dreamweaver MX and Adobe Photoshop 7.0. With this system, the commercializing estate can target a huge market and the technique of marketing and promoting can be more efficient.